EVALUASI PENGGUNAAN ANTIBIOTIK PROFILAKSIS PADA PASIEN BEDAH DI RUMAH SAKIT BALA KESELAMATAN BOKOR DENGAN METODE DEFINE DAILY DOSE DAN GYSSENS - Kirana, Alda Galuh; Susanto, FX Haryanto; Nugraha, Dhanang Prawira (Ma Chung Press, Universitas Ma Chung, 2023)
Infectious diseases remain a significant public health concern, especially in developing countries. Infection involves the transmission and multiplication of infectious agents within the host's body. An infection is a condition caused by pathogenic microorganisms, with or without accompanying clinical symptoms (Ministry of Health of the Republic of Indonesia, 2017). The aim of this study is to provide an overview of surgical patients and the pattern of antibiotic use based on the DDD and Gyssen methods at Bala Keselamatan Bokor Hospital. This observational study was conducted retrospectively by reviewing patients' medical records at the hospital from January 1 to March 31, 2023. The data were then analyzed using the Gyssens and ATC/DDD methods. The results of the study showed that surgical patients have two main characteristics based on age and gender. The highest age range was 56 to 65 years, accounting for (25%) of the cases, with the majority being male, constituting (28%) of the cases. The second-highest age range was 46 to 56 years, making up (23%) of the cases, with females comprising (29%) of the cases. Regarding the evaluation of the quantity of antibiotic use using the ATC/DDD method, the highest DDD value was observed for ceftriaxone with a percentage of (7.6%).